Kinetic study of the photochemical reaction between fluoroxiperfluoromethane and carbon monoxide - Blesa, Miguel Ángel; Aymonino, Pedro J. (Asociación Química Argentina, 1968)
Fil.: Blesa, Miguel Ángel Comisión Nacional de Energía Atómica; Argentina